PENGARUH PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT. BANK MEGA SYARIAH CABANG PASAR SUKARAMAI PEKANBARU - Weni Effri Riati; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Employees are the most important factors which will affect the company in the achievement of its objectives. Many things must be done by the company in order to get good performance. In this case the incentive is so important for all employees so that employees are more enthusiastic and have a good performance. The purpose of this study was to determine how the incentive effect on the performance of employees at PT. Bank Mega Syariah branch Sukaramai Market Pekanbaru.This research was conducted at PT. Bank Mega Syariah Sukaramai Market Pekanbaru branch offices in Pekanbaru patchouli road. Reasons for the selection of research here is due to the large number of employees out annually in PT. Bank Mega Syariah branch Sukaramai Market Pekanbaru.The population in this penenlitian are all employees of PT. Bank Mega Syariah branch Sukaramai Market Pekanbaru, as many as 36 employees. And the entire population is made in the sample. It can be shown from the level of employee loyalty is very high.Keywords: Effect, Incentives, Employee.